(untitled) (Research, Society and Development, 2022)
The medicinal plants and the “garrafadas” ones are among the main therapeutic resources of popular medicine that have been used for a long time by a part of the Brazilian population without health care. In this sense, this article seeks to carry out an integrative review of the literature on the use of medicinal and bottled plants for therapeutic purposes in the Brazilian Semiarid. For the survey of two articles, the following bases are used: Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), CAPES/MEC Newspaper Portal and Google Scholar. Foram used, to search for two items, the following descriptors and their combinations in the Portuguese, Spanish and English languages: “Garrafadas”, “Plantas Medicinais”, “Terapêutico”. The results show that the population of the Brazilian Semiarid has a historical link with the use of carafes and medicinal plants. These plants and carafes are traded in almost all the cities of the Northeast, with therapeutic purposes, curing pathologies and consolidating physical, mental and low-cost well-being, still helping the family income of two so-called raizeiros. It was concluded that the enormous range of purposes attributed to the bottles is evident, from avoiding pregnancy to cancer treatment. But it is important to highlight that these bottles are usually composed of various medicinal plants that contain active substances that can interact with other drugs to potentiate or prevent certain effects, which can become dangerous or ineffective products.